(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Skin disorder are common manifestation in present era and more so frequent in elder age. The patient of skin disease is more prone to experience physical, emotional and socio-economic embarrassment in the society due to disfigured appearance. Normally 10-15% of the general practitioners encounter with skin disorder in there day to day practice. Vaipadeeka and Charma kustha is a type of Kshudra kustha occurring mainly due to the imbalance of Vata and Kapha doshas resembling the Pityriasis Rubra Pilaris in its clinical manifestation. Pityriasis rubra pilaris is rare chronic disorder that causes hyper keratotic yellowing of the skin including trunk, extremities and particularly palm and sole. The palm and sole become thickened smooth and yellow fissure are common. Systemic corticosteroid, oral retinoid, immunosuppressive such as cyclosporine are the mainstay of treatment of Pityriasis rubra pilaris. The modern treatment modalities are not devoid from grave complication mainly in long term use. Owning these reasons, there is need for treatment having good efficacy and no toxic profile. So this case study was conducted considered ptyriasis rubra pilaris as Charma kustha and Vaipadeeka. Ayurvedic management was planned accordingly. Good result was witness by Virechan and shaman.